Analisis Putusan Mahkamah Agung Tentang Perampasan Barang Hasil Tindak Pidana - Anggito, Tegar Dwi; Sodikin, Sodikin (Journal of Contemporary Law Studies, 2025)
This study aims to analyze in depth the legal aspects of the seizure of evidence by the state in the First Travel case and its implications for the recovery of victims' losses. This study will use normative legal methods, with a qualitative descriptive approach and case studies, to analyze the Supreme Court's decision on the confiscation of goods from criminal acts. The results of the study are expected to provide a significant contribution to the development of a fairer legal system that better supports the rights of victims of crime. The research data will include court decisions, laws and regulations, and relevant legal literature. The urgency of this study is based on the fact that the handling of TPPU must be carried out carefully and cautiously, by paying attention to the principles of justice and protection of victims' rights. The state has an obligation to eradicate crime, but it also has an obligation to protect the rights of its citizens, including the right to receive compensation for losses suffered as a result of criminal acts. This study is expected to provide constructive recommendations for improving the legal system and law enforcement practices in Indonesia, so that a fairer and more effective system can be created in eradicating crime and protecting victims' rights.